2020
DOI: 10.1108/aaaj-09-2016-2697
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Chinese government's political ideology in the field of corporate environmental reporting

Abstract: PurposeIn a state capitalist country such as China, an important influence on company reporting is the government, which can influence company decision-making. The nature and impact of how the Chinese government uses its symbolic power to promote corporate environmental reporting (CER) have been under-studied, and therefore, this paper aims to address this gap in the literature by investigating the various strategies the Chinese government uses to influence CER and how political ideology plays a key role.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 61 publications
(82 reference statements)
0
31
0
Order By: Relevance
“…global pressure, political embeddedness and normative social forces) and organizational internal dynamics (e.g. corporate/family culture, corporate governance and senior/family commitment) (Parsa et al , 2021; Situ et al , 2021; Yin, 2017). Thus, we examine three ownership types: state, local and international.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…global pressure, political embeddedness and normative social forces) and organizational internal dynamics (e.g. corporate/family culture, corporate governance and senior/family commitment) (Parsa et al , 2021; Situ et al , 2021; Yin, 2017). Thus, we examine three ownership types: state, local and international.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…First, state-owned ECEs or SOEs that operate like MNEs emphasize their home country’s regulations and compliance procedures, as they are induced by a concentrated managerial control mechanism (Comyns, 2018). Importantly, the Chinese Government serves as a symbolic source of power and a strong ideologically based political system that influences SOEs’ decision-making in terms of ESG disclosure (Li and Belal, 2018; Situ et al , 2021). In particular, it plays a mediating rather than a coercive role in offering guidance to SOEs to develop globalized ESG reporting to enter global markets and expand their global dominance (Marquis et al , 2017).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in their study of the slavery debate in Antebellum America, Tetlock et al ( 1994 ) found that political ideological leaning affected how the different politicians approached the debate in terms of cognitive style, as well as how this affected their policy preferences. Additionally, other research has shown that U.K. company law was shaped at decisive points in history by the ideological perspectives of the Labour Party (Clift et al, 2000 ; Aguilera & Jackson, 2010 ), and in China, that governmental political orientation influenced the field of corporate environmental reporting (Situ et al, 2021 ). As such, there is significant evidence to show that political ideology does affect the decision-making, and the behaviors, of politicians (Tetlock, 1983 ; Tetlock et al, 1985 , 1994 ), and thus it is likely that they would act on the basis of their filtered impressions woven by their respective political ideological cognitive bases (Jost et al, 2003 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Later, there has been a need to analyze the impact of media reports on government public expenditure and discuss the impact of media monitoring on o cial promotion and local nance (Qi et al, 2016;Chen, 2017;Hanna, 2018). Also, the analysis of the supervision effect of news media in investigating the government's ecological responsibility from the perspective of functional orientation was followed by focusing on the in uence of media monitoring on government transparency and government audit performance (Zhang et al, 2020;Situ et al, 2020;Keppel, 2022).…”
Section: Media Monitoring As a Means Of Governance E Ciencymentioning
confidence: 99%